2020
DOI: 10.3390/s20174957
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency IDentification for Meat Supply-Chain Digitalisation

Abstract: Digitalised supply-chain traceability systems can offer wide prospects both for improving safety as well as enhancing perceived quality. However, the coupling between physical goods and information is often difficult for agri-food items. A solution could be the use of RFID (Radio Frequency IDentification) systems. Due to its wide reading range, Ultra-High Frequency (UHF) technology is already widely used in logistics and warehousing, mostly for the identification of batches of items. A growing interest is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…On the one hand, these examples demonstrate the increased interest of food manufacturers in the trustworthy documentation of their products in a BC [37]. Many companies are already trying to gain the trust of consumers with the help of seals, such as the Fairtrade label, which is given by a Fairtrade organization under certain conditions.…”
Section: Food Supply Chainsmentioning
confidence: 99%
“…On the one hand, these examples demonstrate the increased interest of food manufacturers in the trustworthy documentation of their products in a BC [37]. Many companies are already trying to gain the trust of consumers with the help of seals, such as the Fairtrade label, which is given by a Fairtrade organization under certain conditions.…”
Section: Food Supply Chainsmentioning
confidence: 99%
“…Three papers were found in the Food Cluster that addressed the tracking and tracing of meat (see: [12,28,29]). Barge et al (2020) focus on methods to better mark and identify meat, as they identified the problem of the interface between the physical meat and the digital information.…”
Section: Examples Of Applications and Case Studiesmentioning
confidence: 99%
“…Three papers were found in the Food Cluster that addressed the tracking and tracing of meat (see: [12,28,29]). Barge et al (2020) focus on methods to better mark and identify meat, as they identified the problem of the interface between the physical meat and the digital information. According to Barge et al (2020), increased consumer confidence in food and producer reputation, especially for meat, have been shown to provide increased sales.…”
Section: Examples Of Applications and Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations